Black and White in Church? The legacy of slavery and colonialism - Bakuri, Amisah (Handelingen: Tijdschrift voor Praktische Theologie en Religiewetenschap, 2023)
Black people often feel segregated and excluded in the white dominated churches (Beckford 2011). This raises a lot of questions or personal inquiries (Groenewald 2010; Mosterman 2016): is there ‘oneness’ in the Church or, is there ‘Black and White’ in the Church? Could such experiences explain the disconnectedness and the huge divide between the ‘Dutch’ and the so-called black ‘migrant’ churches? Could this be the main factor for the continuous proliferation of so-called black ‘migrant’ churches in the Netherlands?